The Effectiveness of Distance Learning Using Learning Management System Media and Whatsapp Groups at Senior High School - Agustina, Sinta; Nandiyanto, Asep Bayu Dani (Universitas Pendidikan Indonesia (UPI), 2021)
In the world of education, during the COVID-19 pandemic, schools and colleges were not allowed to do face-to-face learning directly or often called offline at schools or campuses. All teaching and learning processes must be carried out online at home. One alternative to this policy is by applying the Distance Learning (PJJ) method where teachers or students cannot meet face to face directly. PJJ currently carried out is online (in a network) through internet-based media. At the senior high school / vocational school / Islamic Senior High School level PJJ is carried out using a Learning Management System (LMS), which is a system that can manage, convey, and monitor students using an internet-based application. Not enough with LMS, WhatsApp social media using the Group feature is also one of the supports in the successful implementation of online learning during the COVID-19 pandemic. Research on the Effectiveness of Distance Learning (PJJ) using learning media Learning Management System (LMS) and WhatsApp Group was conducted at senior high school 1 Cipeundeuy, Subang, Indonesia.